(untitled) (Bangladesh Journal of Anatomy, 2016)
The mortuary may be a dangerous place. The most dangerous in this environment is the individual himself, who is unaware of its potential hazards. Such peoples are liable to themselves and to others who are working in the mortuary (like Forensic pathologist, Anatomist, Students and staffs). In Bangladesh such safety norms of the mortuary are much lagging behind than the expected international standard. This review focuses particularly on those hazards and risks encountered at the mortuary and to ensure a safe guideline for autopsy workers which seem to be needed to develop a modern mortuary in our country. Bangladesh Journal of Anatomy July 2016, Vol. 14, No. 2, pp. 45-48